Pemberdayaan Kelompok Dasawisma Dalam Peningkatan Ekonomi Melalui Teknologi Budikdamber Di RT 004 Kelurahan Berua Kecamatan Biringkanaya Kota Makassar - Jawiana Saokani; Zul Khairiyah; Frida Alifia (CV. Ulil Albab Corp, 2024)
The Dasawisma Group RT 004 RW 005 is a community group that has a very good organizing spirit. Consists of a group of housewives within RT 004, Berua Village, Biringkanaya District, Makassar City. This group has adequate community and environmental support to develop the potential of housewives to acquire skills and improve the family economy. The aim of this activity is to increase the knowledge, interest and skills of women from the Dasawisma group RT 004 RW 005, Berua Village, Biringkanaya District, Makassar City. The method used was training which contained lectures, questions and answers, providing educational material, the practice of cultivating catfish using a cultivation system in a bucket (budikdamber) and the practice of diversifying processed catfish in the form of nuget and shredded meat. The results obtained are that the women from the Dasawisma group have gained knowledge and skills in making budikdamber, especially catfish commodities.